The relation of abuse to physical and psychological health in adults with developmental disabilities. Issue 2 (April 2019) - ,; Hughes, Rosemary B.; Powers, Laurie E.; Nicolaidis, Christina; Katz, Marsha; Oschwald, Mary; Larson, Darren; Ender, Justice; Plourde, Eddie; Raymaker, Dora; Howard, Lisa; Ashkenazy, Elesia; et al.
Abstract: Background: People with developmental disabilities are at disproportionately high risk of abuse. Although considerable evidence exists on the health-related consequences of abuse in the general population, little is known about those consequences in people with developmental disabilities. Objective: To examine the relation of abuse with psychological and physical health outcomes in adults with developmental disabilities. Methods: We used an accessible audio computer-assisted self-interview to collect anonymous data on demographic and disability characteristics, childhood and adult abuse experiences, and physical and psychological health from 350 women and men with developmental disabilities. Abuse experience was reflected by five factor scores consisting of three child abuse factors (childhood sexual abuse, childhood physical abuse, childhood disability-related abuse) and two adult abuse factors (adult sexual abuse, adult mixed abuse). We examined each of four health outcomes (depression, post trraumatic stress disorder, physical health symptoms, secondary health conditions) separately to determine the extent to which childhood and adult abuse experiences uniquely predicted psychological and physical health outcomes above and beyond demographic and disability-related characteristics. Results: All five abuse factor scores were significantly related to all four health outcomes. When examined simultaneously, childhood disability-related abuse and adult mixed abuse accounted for unique variance in outcomes. Exploratory analyses revealed no difference in the impact of abuse by gender. Conclusions: In this study, childhood disability-related abuse and adult mixed abuse significantly predicted lower levels of psychological and physical health in a sample of adults with developmental disabilities. Our findings highlight the importance of addressing abuse and its sequalae in the developmental disabilities community.